Applying pattern recognition methods plus quantum and physico-chemical molecular descriptors to analyze the anabolic activity of structurally diverse steroids - Alvarez-Ginarte, Yoanna María (Journal of computational chemistry, 2008)
(c) 2007 Wiley Periodicals, Inc.